Analisis Penerapan PSAK No. 409 mengenai Penyajian Laporan Keuangan Dana pada LAZ Insan Madani Jambi - Fadilatul Rohmah; Ahmad Syahrizal; Muthmainnah Muthmainnah (Lembaga Yasin AlSys, 2026)
The management of zakat, infak, and sedekah requires an accountable and transparent accounting system so that entrusted public funds can be professionally reported, while studies that specifically analyze the implementation of PSAK No. 409 as the latest standard in lembaga amil zakat remain relatively limited. This study aims to analyze the implementation of zakat accounting based on PSAK No. 409 at LAZ Insan Madani Jambi and to identify the constraints encountered in its implementation process. The research employed a qualitative approach with a case study design, involving key informants from management and finance staff selected through purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using qualitative descriptive techniques. The findings show that LAZ Insan Madani Jambi has applied the principles of PSAK No. 409 reasonably well in the recognition and measurement of zakat, infak, and sedekah funds, whereby receipts are recognized when cash or non-cash assets are received and distributions are recorded as deductions from funds. However, the implementation of the standard is not yet optimal in terms of financial statement presentation, as the Statement of Cash Flows and Notes to the Financial Statements have not been prepared in accordance with PSAK No. 409 requirements. The study also identifies internal constraints in the form of limited human resource competence in fully understanding the standard, and external constraints in the form of low muzakki literacy regarding the function of financial statements as instruments of accountability. These findings provide practical contributions to strengthening the implementation of PSAK No. 409 in lembaga amil zakat and underscore the importance of enhancing human resource capacity and public education to support transparency and the sustainability of zakat management.